THE SPECIFICS OF WORD-FORMATION PRONOMINAL VOCABULARY IN THE DIALECT OF OLD BELIEVERS NEKRASOV COSSACKS IN STAVROPOL KRAI - V. Gryaznova (Гуманитарные и юридические исследования)
The article deals with the specifics of the word formation of pronominal vocabulary of the Russian dialect of old believers Cossacks-Nekrasov in Stavropol Krai, which, after several centuries of exile, returned in 1962 to Russia and settled in the villages of Levokumsky district, the Stavropol territory. The object of the study is pronominal words, in which the author, along with classical pronouns, includes pronominal adverbs that are similar in meaning and function to traditional pronouns. The subject of the study is the word-formation characteristics of pronominal words of the Cossacks-Nekrasov dialect. The material of the study is recordings of the speech of speakers of the old believers' dialect of the Cossacks-Nekrasov, living in the Levokumsky district of the Stavropol territory, made by the author during ield expeditions. The analysis of the material reveals the implementation of such tendencies in the speech of the Cossacks-Nekrasov in the development of the word-formation system of the national Russian language, which are not supported by the conscious attitudes to normalization characteristic of the literary language. The article uses the material of the pronominal vocabulary of the Cossacks-Nekrasov dialect to describe the facts of violation of non-global prohibitions in the ield of word formation norms, as well as cases of using the resources of the national Russian language. The author identiies pronominal lexemes that are absent in the Russian literary language: ten new word-formatively motivated pronominal adverbs and eleven new motivated demonstrative pronouns, the author also describes models of word-formation of pronominal vocabulary that do not exist in the Russian literary language and are peculiar only to the speech of the old believers of the Cossacks-Nekrasov of the Stavropol territory. These include preixal, preixal-sufixal, preixal-postixal, postixal models, word-formation game, and pure addition models. The article emphasizes that all these word-forming models are not described in such a fundamental work as Russian grammar-80, which does not even have a section dedicated to the word-formation of pronouns.